Sri Lanka - Zimmermann, Robert (Robert B.) (Chicago : Childrens Press, 1992)
Describes the geography, history, culture, industry, and people of Sri Lanka.
Includes index.
Wilson's Junior High School.
7.1
5-8
5-9.
Keywords: Sri Lanka -- Juvenile literature; Sri Lanka; Sri Lanka